Juvenile bovine bone is an appropriate surrogate for normal and reduced density human bone in biomechanical testing: a validation study - Fletcher, J. W. A.; Williams, S.; Whitehouse, M. R.; Gill, H. S.; Preatoni, E. (Scientific reports, 2018)
Orthopaedic research necessitates accurate and reliable models of human bone to enable biomechanical discoveries and translation into clinical scenarios. Juvenile bovine bone is postulated to be a potential model of normal human bone given its dimensions and comparatively reduced ethical restrictions. Demineralisation techniques can reduce bone density and alter bone properties, and methods to model osteoporotic bone using demineralised juvenile bovine bone are investigated. Juvenile bovine long bones were quantitatively CT scanned to assess bone density. Demineralisation using hydrochloric acid (0.6, 1.2 and 2.4 M) was performed to create different bone density models which underwent biomechanical validation for normal and osteoporotic bone models. All long bones were found to have comparable features to normal human bone including bone density (1.96 ± 0.08 gcm −3 ), screw insertion torque and pullout strength. Demineralisation significantly reduced bone density and pullout strength for all types, with 0.6 M hydrochloric acid creating reductions of 25% and 71% respectively. Juvenile bovine bone is inexpensive, easy to source and not subject to extensive ethical procedures. This study establishes for the first time, the use of its long bones as surrogates for both normal and osteoporotic human specimens and offers preliminary validation for its use in biomechanical testing.